NIR-activated catechol-functionalized nanodiamond nanofibers for accelerating on-demand MRSA and E. coli biofilm eradication - Hyeonseo Park; Tejal V. Patil; Jieun Lee; Hojin Kim; Seong-Jun Cho; Ki-Taek Lim (Journal of Biological Engineering)
Abstract The rise of antibiotic resistance has made bacterial infections a persistent global health issue. In particular, extracellular polymeric substances (EPS) secreted by bacteria limit the effectiveness of conventional antibiotics, making biofilm removal challenging. To address this, we created ND@PDA nanoparticles by coating the surface of nanodiamonds (ND) with polydopamine (PDA). These nanoparticles were then integrated into polyvinyl alcohol to fabricate PVA/ND@PDA nanofiber scaffolds, resulting in an innovative platform with enhanced photothermal, antibacterial and antibiofilm properties. Upon exposure to near-infrared (NIR) light, the scaffolds exhibited a significant photothermal activity, oxidative stress and effectively damaging key bacterial components, such as biofilm, bacterial membranes, and proteins. Additionally, the catechol groups in PDA provided strong cell adhesion and high biocompatibility on the nanofiber surface. Our research proposes a platform that not only effectively addresses antibiotic-resistant infections but also contributes to advancements in wound healing therapies by enabling controlled antibacterial action with minimal toxicity.